Survey and morphological study of Vanya Silk moths in the forest of district Bageshwar of Uttarakhand - Paliwal, D. P.; Joshi, Garima; Chandrakanta, Chandrakanta; Kumar, Mahesh; Paliwal, A. K. (Indian Journal of Hill Farming, 2017)
The present study deals with the diversity of wild silk moths in the forests of District Bageshwar, Uttarakhand. As the forests of the District Bageshwar cover tropical to temperate forest plant species in which sericiginous insects are found profusely. In connection of wild moth collection, a periodical survey was conducted during the year 2012-13, which revealed availability of three species viz, Actias selene Hubner, Antheraea assama Westwood and Samia cynthia (Drury) from Lepidoptera: Saturniidae found in the forest of District Bageshwar, Uttarakhand.